The Effect of Arrum Product Financing on Profit Income - Dewi, Erna (Institut Bisnis dan Informatika Kesatuan, 2024)
Arrum is a sharia loan scheme aimed at entrepreneurs with payments made in installments. Where the collateral that can be used is the Motor Vehicle Owner's Book (Buku Pemilik Kendaraan Bermotor/BPKB) for a car or motorbike, as well as gold. This research aims to examine the extent to which Arrum product financing influences profit generation at the Meulaboh branch of PT Pegadaian Syariah. The research method used in this research is a quantitative method. The type of data used in this research is secondary data. The population used in this research were customers of the Meulaboh branch of Pegadaian Syariah with a population of 250 people. Purposive sampling is the data collection method used in this research, namely 100 people. The analysis technique used in this research is regression analysis. The results of statistical research show that Arrum products have a positive and significant influence on profit generation at PT. Sharia Pawnshop Meulaboh Branch.